Metabolic dysfunction-associated fatty liver disease: a year in review. Issue 3 (9th May 2022) - Alharthi, Jawaher; Gastaldelli, Amalia; Cua, Ian Homer; Ghazinian, Hasmik; Eslam, Mohammed
Abstract : Purpose of review: In 2020, a novel comprehensive redefinition of fatty liver disease was proposed by an international panel of experts. This review aims to explore current evidence regarding the impact of this new definition on the current understanding of the epidemiology, pathogenesis, diagnosis, and clinical trials for fatty liver disease. Recent findings: The effectiveness of metabolic dysfunction-associated fatty liver disease (MAFLD) was compared to the existing criteria for nonalcoholic fatty liver disease (NAFLD). Recent data robustly suggest the superior utility of MAFLD in identifying patients at high risk for metabolic dysfunction, the hepatic and extra-hepatic complications, as well as those who would benefit from genetic testing, including patients with concomitant liver diseases. This change in name and criteria also appears to have improved disease awareness among patients and physicians. Summary: The transformation in name and definition from NAFLD to MAFLD represents an important milestone, which indicates significant tangible progress towards a more inclusive, equitable, and patient-centred approach to addressing the profound challenges of this disease. Growing evidence has illustrated the broader and specific contexts that have tremendous potential for positively influencing the diagnosis and treatment. In addition, the momentum accompanying this name change has included widespread public attention to the unique burden of this previously underappreciated disease.